2023
DOI: 10.1088/1674-4926/44/6/061801
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of recent progress on enhancement-mode β-Ga2O3 FETs: Growth, devices and properties

Abstract: Power electronic devices are of great importance in modern society. After decades of development, Si power devices have approached their material limits with only incremental improvements and large conversion losses. As the demand for electronic components with high efficiency dramatically increasing, new materials are needed for power device fabrication. Beta-phase gallium oxide, an ultra-wide bandgap semiconductor, has been considered as a promising candidate, and various β-Ga2O3 power devices with high brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…However, they are limited in their breakdown voltage and small sample size. SOI FETs should be considered as a proof of concept with the intent to apply successful designs into bulk devices; (7) Novel structures simulated through TCAD, such as vertical trench gates, GAA, air-gap FPs, HBTs, and others, should be used to evaluate the potential of a design before fabrication; (8) RF FETs have been realized in delta-doped MESFETs, AlGO/GO MODFETs, and HFETs, forming a 2DEG with Si-doped AlGO/UID-GO; (9) One commonality of RF FETs is their T-gate structure, allowing highly scaled L G while maintaining low noise figures; (10) RF FETs have reported high operating frequencies at ≥27 GHz with and without FP dielectrics; (11) Ohmic contacts should always utilize some improvements, such as regrowth, ion implantation, or interlayers; (12) P-NiO-gate dielectrics show promise in increasing the BFOM, while maintaining highquality/low-defect density interfaces. A high-bandgap dielectric should be added to increase the gate swing beyond the pn turn-on voltage;…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they are limited in their breakdown voltage and small sample size. SOI FETs should be considered as a proof of concept with the intent to apply successful designs into bulk devices; (7) Novel structures simulated through TCAD, such as vertical trench gates, GAA, air-gap FPs, HBTs, and others, should be used to evaluate the potential of a design before fabrication; (8) RF FETs have been realized in delta-doped MESFETs, AlGO/GO MODFETs, and HFETs, forming a 2DEG with Si-doped AlGO/UID-GO; (9) One commonality of RF FETs is their T-gate structure, allowing highly scaled L G while maintaining low noise figures; (10) RF FETs have reported high operating frequencies at ≥27 GHz with and without FP dielectrics; (11) Ohmic contacts should always utilize some improvements, such as regrowth, ion implantation, or interlayers; (12) P-NiO-gate dielectrics show promise in increasing the BFOM, while maintaining highquality/low-defect density interfaces. A high-bandgap dielectric should be added to increase the gate swing beyond the pn turn-on voltage;…”
Section: Discussionmentioning
confidence: 99%
“…Previous review articles on β-Ga 2 O 3 FETs have reported the chronological development in device design and performance [10], or focused specifically on RF FETs [7], E-mode FETs [11], or vertical GaN and β-Ga 2 O 3 FETs [9]. Other review papers have covered FETs designed for both high-power and RF applications [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Band gap for β-Ga 2 O 3 [11] 4.85 eV Band gap for diamond [26] 5.45 eV Electron affinity energy for β-Ga 2 O 3 [26] 4 eV Electron affinity energy for diamond [26] 1.67 eV Fin electron mobility [16] 30 cm 2 Vs −1 Drift region electron mobility [16] 60 cm 2 Vs −1 Bulk β-Ga 2 O 3 electron mobility [16] 150 cm 2 Vs −1 PCD hole mobility [ [18] −1.2 [010] −1 [001] Thermal conductivity for PCD [31] 120 W mK −1 Thermal conductivity for PCD nucleation layer [31] 50 W mK −1 Temperature dependent decay coefficient α of thermal conductivity for PCD [21] −0.45…”
Section: Model Parameters Values Unitsmentioning
confidence: 99%
“…In recent years, most research on β-Ga 2 O 3 transistors is lateral MOS structures [8][9][10]. Nonetheless, the absence of p-type Ga 2 O 3 presents a substantial obstacle in achieving E-mode for lateral devices, as the gate control capability is insufficient to entirely deplete the channel [11]. As a solution, recessed-gate structure has been implemented to achieve E-mode lateral MOSFETs [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of different post-annealing gas conditions was investigated for radio frequency magnetron sputtering prepared Sn-doped β-Ga 2 O 3 films. Y. Wang and co-workers [6] developed a CVD method for centimetre-scale Ga 2 O 3 microwire growth and demonstrated photodetectors based on the fabricated Ga 2 O 3 microwires. They show that microwires of single crystalline Ga 2 O 3 can be obtained reaching up to 1 cm in length.…”
mentioning
confidence: 99%